Prediction of Euclidean distance between existing and target product for software product line testing using FeatureIDE. (17th December 2021) - Saini, Ashish; Kumar, Raj; Kumar, Satendra; Mittal, Mohit
Software product line (SPL) is a paradigm that consists a family of products, all these products have some common features. SPL contains enormous products due to variable features, to test all of them is unfeasible. For this reason, several methods have been introduced to test the product line. These methods are used to prioritise products because they are based on feature interaction and do not provide information regarding products' validity. To check the validity of products, we introduce a method based on Euclidean distance, which verifies the product based on the calculated distance between the real and desired product features. In addition, we compare the proposed method with the existing interaction-based method for product lines of different sizes. The results show that the proposed method takes less time to test the effectiveness of the product and increases the impact of the method in terms of time.